AuCu/TiO2 Catalysts prepared using electron beam irradiation for the preferential oxidation of carbon monoxide in hydrogen-rich mixtures (Brazilian Journal of Radiation Sciences, 2021)
The major part of the world production of hydrogen (H2) is originated from a combination of methane steam reforming and water-gas shift reaction resulting in an H2-rich mixture known as reformate gas, which contains about 1% vol (10,000 ppm) of carbon monoxide (CO). The preferential oxidation reaction of CO in H2-rich mixtures (CO-PROX) has been considered a very promising process for H2 purification, reducing CO for values below 50 ppm allowing its use in PEMFC Fuel Cells. Au nanoparticles supported on TiO2 (Au/TiO2) catalysts have been shown good activity and selectivity for CO-PROX reaction in the temperature range between 20-80 ºC; however, the catalytic activity strongly depends on the preparation method. Also, the addition of Cu to the Au/TiO2 catalyst could increase the activity and selectivity for CO-PROX reaction. In this work, AuCu/TiO2 catalysts with composition 0.5%Au0.5%Cu/TiO2 were prepared in a single step using electron beam irradiation, where the Au3+ and Cu2+ ions were dissolved in water/2-propanol solution, the TiO2 support was dispersed and the obtained mixture was irradiated under stirring at room temperature using different dose rates (8 – 64 kGy s-1) and total doses (144 – 576 kGy). The catalysts were characterized by energy dispersive X-ray analysis, X-ray diffraction transmission electron microscopy, temperature-programmed reduction and tested for CO-PROX reaction.  The best result was obtained with a catalyst prepared with a dose rate of 64 kGy s-1 and a total dose of 576 kGy showed a CO conversion of 45% and a CO2 selectivity of 30% at 150 oC.
Keywords: hydrogen; catalyst; CO-PROX